Oral history in USM library: supporting reference and research needs - Fesal, Fujica Azura; Mohamad, Radia Banu Jan; Jaafar, Cik Ramlah Che; Jan, Noor Azlinda Wan (Persatuan Sejarah Lisan Malaysia dan Pertubuhan Pentadbiran Wilayah Satun, 2016)
Oral history has usually referred to as an account of historical event, person or place, a first person memory of the past, by an eyewitness. It is regarded as living memories which have great importance in the history of mankind. It has also become a key resource for reconstructing, recreating and recording past and present knowledge of society. Academic libraries have assisted as repositories for books and manuscripts that support in revealing the stories of world’s civilization for centuries. The compilation of oral history at the library could help in reference and research if only the effort to record, document, preserve and promote information resources are well planned. Current technology could be of great help to be utilized in relaying the access to the researchers. Through institutional repositories, the visibility of the information could be increased. This paper will explain the importance of oral history, the background of the collection at USM Library and the initiatives taken to promote it as the primary and reliable sources that could play a role in historical research activities in the future.